Social Problems and Social Control in Criminal Justice - Burns, Stacy Lee (Lynne Rienner Publishers, 2022)
Today's headlines are rife with reports of hate crimes, domestic terrorism, drug abuse, police malfeasance, and many other profound social problems. Equally, there are discussions, often contentious, about how best to respond to the issues raised. Stacy Burns and Mark Peyrot explore government efforts to address social problems in the context of the criminal justice system. Adopting an institutionalist perspective, the authors show how social control efforts have adapted and changed over time--and how some efforts have inadvertently contributed to the problems they are trying to alleviate. Their work draws on a wealth of sources, ranging from case law to popular initiatives to policy analysis, to advance both theoretical and practical understanding of criminal justice at work.